(untitled) (Journal of the College of Basic Education, 2022)
The aim of the current research is to identify the effect of (Lee) cognitive strategy on the achievement of students of the Department of Art Education in the subject of art history and to measure the effect of the cognitive strategy (Lee) on the achievement of students of the Department of Art Education in the subject of Art History. The researcher appointed two of the four halls representing the first stage of the application of the research experiment with (30) male and female students for each hall, as the number of the two groups reached (60) male and female students for the academic year (2020-2021). Experimental In order to achieve the research hypotheses, the equivalence of the two research groups was verified in the variables (the chronological age of the students calculated in months, the pre-test scores, the academic achievement of the fathers and mothers, the intelligence test). The goal set to measure The results of the current research showed that the students of the experimental group who studied art history according to the (Lee) cognitive strategy outperformed the students of the control group who studied according to the usual method.